Analysis of Organizational Readiness for The Implementation of Environmental, Social and Governance (ESG) in The Development of Green Laboratories at Pertamina Central Hospital Jakarta - Dian Wahyu Rofita Kusuma; Alih Germas Kodyat; Haidar Istiqlal (International Journal of Health and Pharmaceutical (IJHP), 2026)
The transformation of the healthcare sector toward sustainability has become a strategic necessity due to the high emissions generated by healthcare service activities, particularly hospital laboratories. The integration of Environmental, Social, and Governance (ESG) principles through the development of green laboratories represents a key approach to achieving sustainable healthcare. This study aims to analyze the organizational readiness of Pertamina Central Hospital (RSPP) in implementing ESG, focusing on regulatory, human resource, and infrastructure aspects. This study employed a descriptive qualitative design. Data were collected through field observations, document reviews, in-depth interviews, and Focus Group Discussions (FGDs). Data analysis was conducted through data reduction, narrative and thematic presentation, and conclusion drawing, which were validated using source and method triangulation. The results indicate that regulatory support for green laboratories is available but incomplete. In the human resource aspect, occupational safety and environmental culture have been implemented; however, conceptual understanding of green laboratory principles has not been evenly distributed among staff. Supporting infrastructure is partially available, yet energy efficiency technologies and environmental sensor systems have not been fully implemented. The organizational readiness of RSPP in implementing ESG for green laboratory development has been partially established. Strengthening formal regulations, enhancing human resource capacity through structured training, and developing green technology-based infrastructure are required as sustainable.